Il “corpo proprio” e il sentire in comune: Empfindung, Einfühlung, Mitgefühl. La dinamica del sentire e la questione dell’empatia fra Sulzer ed Herder - Tedesco, Salvatore (Bollettino Filosofico, 2022)
The contribution aims to identify some theoretical lines that cross the German Enlightenment reflection from Leibniz and Wolff to Herder, focusing on the relationship between oneself and otherness, between the dimension of “one’s own body” and the theme of “feeling in common”. Thus, we propose to identify some of the flow lines along which reflection on empathy develops. Keywords: Empathy, German Enlightenment, Herder, Self and Otherness, Sulzer